Modulation of Gastrointestinal Mucus Properties with Ionic Liquids for Drug Delivery. Issue 13 (29th May 2021) - Peng, Kevin; Gao, Yongsheng; Angsantikul, Pavimol; LaBarbiera, Anthony; Goetz, Morgan; Curreri, Alexander M.; Rodrigues, Danika; Tanner, Eden E. L.; Mitragotri, Samir
Abstract: The mucus barrier lining the gastrointestinal tract poses a significant barrier to the oral delivery of macromolecular drugs. Successful approaches to overcoming this barrier have primarily focused on reducing drug and carrier interactions with mucus or disrupting the mucus layer directly. Choline‐based ionic liquids (ILs) such as choline geranate and choline glycolate (CGLY) have recently been shown to be effective in enhancing the intestinal absorption of macromolecules such as insulin and immunoglobulin (IgG), respectively. Herein, the use of choline‐based ILs as mucus‐modulating agents for safely improving drug penetration through mucus is described. Choline‐based ILs significantly increase the diffusion rates of cationic dextrans through mucin solution. Choline‐maleic acid (CMLC 2:1) enhances the diffusion of 4 kDa cationic dextran in mucin solution by more than fourfold when compared to phosphate‐buffered saline control. Choline‐based ILs also reduce mucus viscosity without significantly impacting the native mucus gel structure. In vitro studies in a mucus‐secreting coculture model with Caco‐2 and HT29MTX‐E12 cells further demonstrate the effectiveness of ILs in improving transport of cationic molecules in the presence of secreted mucus. This work demonstrates the potential for choline‐based ionic liquids to be used as nondestructive mucus‐modulating agents for enabling enhanced oral delivery of macromolecular drugs. Abstract : The mucus layer is a significant barrier to drugs delivered orally. Macromolecular drugs and cationic molecules have a difficult time in particular passing through the mucus layer without becoming stuck. Choline‐based ionic liquids are used as mucus‐modulating agents, increasing molecular diffusion without significantly disrupting the native mucus structure.